2019
DOI: 10.1021/acs.organomet.9b00226
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Photochemical Transformations of Chromium(I) 1,3 Bis(diphenylphosphino), [Cr(CO)4(dppp)]+, by EPR Spectroscopy

Abstract: UV-induced photochemical transformations of the paramagnetic [Cr­(CO)4(Ph2PCH2CH2CH2PPh2)]+ complex (abbreviated [Cr­(CO)4(dppp)]+) in dichloromethane was investigated by CW EPR spectroscopy. Room-temperature UV irradiation results in the rapid transformation of [Cr­(CO)4(dppp)]+ into trans-[Cr­(CO)2(dppp)2]+. However, low-temperature (77–120 K) UV irradiation reveals the presence of an intermediate mer-[Cr­(CO)3(κ1-dppp)­(κ2-dppp)]+ complex which photochemically transforms into trans-[Cr­(CO)2(dppp)2]+. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Together these results imply that the major reduction products obtained by using Cp* 2 Co and Al-based reductants are integer-spin, non-Kramers Cr II (d 4 , S = 2) species that are not directly observable in our cases by X-band EPR. We conclude that the small signal observed near g = 2 upon chemical reduction, however, is a minor Cr I product that arises via a minor reaction pathway about which little evidence is available. , …”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Together these results imply that the major reduction products obtained by using Cp* 2 Co and Al-based reductants are integer-spin, non-Kramers Cr II (d 4 , S = 2) species that are not directly observable in our cases by X-band EPR. We conclude that the small signal observed near g = 2 upon chemical reduction, however, is a minor Cr I product that arises via a minor reaction pathway about which little evidence is available. , …”
Section: Resultsmentioning
confidence: 77%
“…The collected EPR data for the in situ chemical reductions were analyzed by using the validated QEPR assay to determine the concentration of the Cr I species , formed upon reduction ( vide supra ). Our findings show that reduction results in <1% conversion to the species assigned as Cr I with respect to the concentration of the Cr III starting material used in each case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A CW EPR study was therefore recently reported on the UV activation of a [Cr(CO) 4 (Ph 2 P(CH 2 ) 3 PPh 2 )] 1 complex. 120 In general there is very little literature on the photochemistry of Cr 11 systems, 120 despite the copious amount of literature available on the analogous Cr 0 complexes; this is likely due to the air sensitive nature of the Cr 11 systems. UV photolysis of the [Cr(CO) 4 (Ph 2 P(CH 2 ) 3 PPh 2 )] 1 complex breaks both the Cr-CO and Cr-P bonds, ultimately leading to the formation of a dicarbonyl [Cr(CO) 2 (Ph 2 P(CH 2 ) 3 PPh 2 ) 2 ] 1 complex and a mer-[Cr(CO) 3 -(Ph 2 P(CH 2 ) 3 PPh 2 ) 2 ] 1 complex which is an intermediate observed only at low temperature.…”
Section: Oligomerisation Based Systemsmentioning
confidence: 99%